Selective deficits in cognition and memory in high-functioning parkinsonian patients. Issue 7 (July 1990) - Mohr, E; Juncos, J; Cox, C; Litvan, I; Fedio, P; Chase, T N
Abstract : To evaluate the profile and extent of cognitive deficits in Parkinson's disease, afflicted patients of exceptional professional distinction, who continue to function successfully in leadership positions, were compared neuropsychologically to neurologically normal individuals, matched for sex, age, education and professional standing. While patients showed relative preservation of verbal skills and higher executive function, they exhibited a significant reduction in episodic memory and visuospatial function. The observation of circumscribed impairment in this select group of Parkinsonian patients further implicates cognitive and memory deficits as consistent features of Parkinson's disease.